Do eye movements reflect readers’ thoughts during reading? Evidence from multidimensional experience sampling and eye movements - Mézière, Diane; Kaakinen, Johanna K.; Ranta, Emilia; Kukkonen, Karin; Smallwood, Jonathan; Simola, Jaana (Academic Press Inc., 2026)
While reading narrative texts, readers’ attention often fluctuates from the text (e.g., immersion) to text-unrelated thoughts (e.g., mind-wandering). Research on mind-wandering and immersion suggests that they influence the reading process differently. In this article, we examine the types of thoughts readers have while reading a literary text. Specifically, we investigated the effect of immersion and mind-wandering on eye-movement behaviour during reading. Fifty-six participants read extracts from a novel while their eye-movements were monitored. Participants’ thoughts were probed using multidimensional experience sampling. We identified four types of thought: Immersion, Mind-wandering, Sub-Vocalization, and Social Episodic Thoughts. We then ran General Additive Mixed Models (GAMMs) to examine the relationship between these thought types and eye movements. Results show that eye movements are influenced by the types of thoughts readers experience while reading literary texts. These results have important implications for the way that mind-wandering is typically investigated, particularly in reading research.